New urban settlements in a perspective of public and private interests - Marcus Adolphson (European Regional Science Association (ERSA), 2004)
Changes of land use pattern and urban form could be seen as a dynamic result of the trade off by public and private interests. Private interest – individual residents or firms – tries, according to micro economic theory, to maximize their individual utility. Public interests – conveyed by government institutions on different geographical levels - on the other hand, try according to macro economic theories to maximize the general welfare in a community according to the preferences of the political system. The focus is to measure the importance of spatial locations factors regarding new residential and commercial buildings in relation to the existing urban form, political guidelines and ecological features. In the region transportation infrastructure systems, as high speed commuting train and highways, have been implemented in the middle of the period. The time period investigated is 1992-2000. The importances of the location factors were obtained by logistic regression analysis and transformation of the ß -values into elasticities. The dependent variables were settlements of new urban elements in pixels of 50*50 meters. Independent variables where distances to existing urban elements, presence of public interests and some ecological features as south faced hill slopes, distance to water areas and geology. Results from this projects reveals that new urban settlements in general are located in proximity to existing urban settlements of the same kind, in remotness to existing urban focal points and to some extend within planned areas. National/regional transportation nodes do not have any apparent influence on the location. A general conclusion from this investigation is that the built environment develops towards a further dispersed rural spatial pattern though with some correspondence to the comprehensive land use plan.
Keywords: 330